(3KHJ GdOhGfi aj YO eTGjNI hGdYdhe GdJi JdbGgG efge heSGFd aj CUhd Gdabg hGdMOjKs - (3LdGd GdOjf eMeO Hf CSYO GdUOjbj GdOhGfj, GdOhGfj,J (B918 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GPi LYd GdSdWGf ZjGKG ddeSJZjKjf CeG HYO ajbhd eMeO Hf CSYO GdOhGfi GdUOjbi Efi cfJ HQgg ef GdReGf eTZhakG HCf CSdc ai Sdc NOGe MVQI ef aGb SdGWjf GdCjGe CYfi GdSdWGf Hf GdSdWGf GdeSFdI GdChdi ai CUhd GdMOjK hGdabg s
(3BNQgG (B:s
(3hGdHGA EPG hbY ai GdeQJHI GdKGdKI hgh eQJHI GdeHGJ cGf QBA hbhdg HGHGQG dWjaI dG JNai Yf GdaWf gPG BNQ eG bUOfG EjQGOg ai gPg GdQSGdI LYdJg fehPLkG dJdc GdYdhe djfXQ NOGe GdYJHI GdChdi ajg HYjf GdQVG hgh fgGjI GdeSFhd hZGjI Gdefi hddg GdMeO as
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B32s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdeLGejYs